Doing Business Economy Profile 2015 : Nicaragua - World Bank Group (Washington, DC, 2015)
This economy profile for Doing Business 2015 presents the 11 Doing Business indicators for Nicaragua. To allow for useful comparison, the profile also provides data for other selected economies (comparator economies) for each indicator. Doing Business 2015 is the 12th edition in a series of annual reports measuring the regulations that enhance business activity and those that constrain it. Economies are ranked on their ease of doing business; for 2015 Nicaragua ranks 119. A high ease of doing business ranking means the regulatory environment is more conducive to the starting and operation of a local firm. Doing Business presents quantitative indicators on business regulations and the protection of property rights that can be compared across 189 economies from Afghanistan to Zimbabwe and over time. Doing Business measures regulations affecting 11 areas of the life of a business known as indicators. Ten of these areas are included in this year's ranking on the ease of doing business: starting a business, dealing with construction permits, getting electricity, registering property, getting credit, protecting minority investors, paying taxes, trading across borders, enforcing contracts, and resolving insolvency. Doing Business also measures labor market regulation, which is not included in this year's ranking. The data in this report are current as of June 1, 2014 (except for the paying taxes indicators, which cover the period from January to December 2013).